Loyalty Point Reward System Using Blockchain : (Case Study in PT XYZ) - Florian Kurniadhi, Yosep Wahjudi, Abdul Rahman, Emil R. Kaburuan, Gunawan Wang, Sfenrianto (International Journal of Control and Automation, 2020)
Blockchain is one of the newest digital technology platforms that build on cloud and can be used as a secure and reliable data platform exchange between one company to another. PT XYZ is a company group, as a company group, PT XYZ have a lot of child company that spread in all business sector like banking, housing, assurance, health, and palm oil industry. Each child company have their own loyalty point reward system, but the data and point can’t be used and exchange across the child company. The purpose of this research is to design a new secure loyalty point reward system that can exchange data and point between one child company to another child company of PT XYZ.  The new design of loyalty point reward system will provide a new concept of digital IT architecture where data can be integrated between one company to another. This new design and concept can be used as a foundation for further analysis and implementation of loyalty point reward system in PT XYZ. This paper can also be a reference for another blockchain implementation in another industries.